Cultural Words in Sacral Text and their Translation: Linguistic and Extra-Linguistic Factors - Georgy T Khukhuni; Irina I Valuitseva; Anna A Osipova (Russian journal of linguistics: Vestnik RUDN, 2019)
The purpose of this article is to study the issue of key features of the so-called cultural words (realia) in sacred texts (the Bible is taken as an example) as well as a distinctive nature of their cross-language transfer. This problem is essential not only for the Bible translation as such but it also enables to clarify some aspects related to the representation of the vocabulary with cultural identity in the target language that is explained by the very nature of the Old and New Testaments containing a wide variety of the realia that refer directly to a religious cult and to the everyday life of Palestinian people and their neighborhood in the Bible times. The material for the present research includes versions of the Holy Writ created in different periods in a number of languages (Latin, Church Slavonic, Russian and English). While analyzing, the classical translations labelled often as “national” ones have been used (the King James Bible, Synodal Translation), as well and the versions created in the 20th and 21st centuries. The main approach applied herein is the identifying of the corresponding units in the said Bible texts, the ascertainment of the possibility of their ambivalent interpretation, the correlation within the considered versions of translation, the determination of translation strategies used for representing the realia and their comparative analysis. When considering the options presented, special attention has been paid to extra-linguistic factors, since they often play a decisive role in solving the said task. The key results of the made survey can be formulated as follows: 1) since translations could have been made from different versions of the source text, there are cases when certain realia are available in some translations but are missing in others; 2) the use of transcription / transliteration of the realia in Russian versions of the Old Testament in some cases is determined by their representation in the Greek and Church Slavonic texts of the Bible and therefore in both the Synodal and the new translations they can be presented in a form different from that available in European languages; 3) the representation of the Greek word diopetês ( fallen from heaven ) as the proper name Diopet in the Synodal Translation is usually qualified as an elementary mistake, but it could have been also provoked by an intention to follow Greek and Church Slavonic traditions; 4) the existence of the so-called ‘undefined realia’ in the source text, an exact meaning of which is not known, causes their various interpretations in the target language; 5) during the analysis of the units of the target language used in the translation of the Holy Writ, the diachronic aspect must be taken into account considering, on the one hand, the possibility of losing or changing the meaning in the course of linguistic evolution, and on the other hand, avoiding vesting the reality with the meaning that it could not have; 6) a number of translations made in recent decades are characterized by a pronounced pragmatic orientation, in some cases causing a significant neutralization of the national-cultural specificity or its adaptation to the corresponding cultural environment, the degree of admissibility of which in some cases is controversial. The above items enable to clarify a number of aspects related to the methods of translating the realia and the importance of such aspects for attaining the translation adequacy.